Peramalan Jumlah Kunjungan Wisatawan Mancanegara Ke Indonesia Menggunakan Autoregressive Integrated Moving Average (ARIMA) - Ramadhani, Adelia; Wahyuningsih, Sri; Siringoringo, Meiliyani (EKSPONENSIAL, 2022)
Autoregressive Moving Average (ARIMA) is a general model that is often used in time series modeling. One application of ARIMA can be used on the data foreign tourist visits to Indonesia. The tourism sector is one of the priority sectors in Indonesia's economic development. One of the determining factors in the tourism sector is the number of foreign tourist visits. Therefore, forecasting the number of foreign tourist visits is very necessary. The purpose of this study was to obtain a model and forecast results for the number of foreign tourist visits from March 2020 to October 2021 using the ARIMA model. The results of the analysis showed that the ARIMA model (0,1,1) was the best model with a MAPE of 6.23%. The forecasting results with the best model showed that the highest number of foreign tourist visits is in Agustus 2021 and the lowest is in December 2020.